(untitled) (Research, Society and Development, 2020)
Anchorage has always been one of the limitations of orthodontics and in almost all orthodontic therapy, it is necessary to obtain it. With the discovery of osseous integration, a new anchoring model, the skeletal model, emerged. In an extra alveolar skeletal anchorage, the more oblique positioning of the mini-screws can increase the risk of deformation. The objective of this work was to analyze, in an in vitro study, the mechanical performance in the insertion and removal torques and to observe if the type of alloy and the insertion angles influence the use of these mini-screws in extra alveolar positions. 40 mini-screws of similar diameter and length (2.0x12mm), but of different alloys (20 of steel and 20 of titanium) were used, all inserted by a digital torque wrench in synthetic polyurethane bone cortex (40PCF). The insertions were made in two angles, one at 30º and the other from 60º to 30º. After obtaining the data, they were subjected to statistical analysis of variance, Generalized Estimation Equations, with a 95% confidence level and a 5% significance level. Statistical differences were observed in the analyzed factors. Among the factors analyzed, type of alloy and angulation of insertion, and with the data obtained we can conclude that regardless of the alloy, angulation is an essential factor in increasing the torques.